Analisa Keserasian Armada untuk Mencapai Produksi Armada yang Optimum di PT Nunukan Bara Sentosa Satu, Desa Sebakis, Kecamatan Nunukan, Kabupaten Nunukan, Provinsi Kalimantan Utara - Muhamad Awaludin; Iswandaru; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Nunukan Bara Santosa Satu (NBSS) is a private company owned by Medco Minning with commodities that produce coal, mining, processing and further marketing of coal commodities located in Sebakis Village, Nunukan District, Nunukan Regency, North Kalimantan Province, to support the mining process, at the Ambu site using a means of transportation with the Sany SKT 90 Dump Truck type with a Sany 750H digging tool, with the open pit open pit mining method, so that in all mining activities there are factors that are difficult to avoid, namely the weather, if it rains it will result in The cessation of production was due to the condition of the road being still soiled and the handling of the slipperly still lacking units, but this can be covered by sunny weather conditions. For this reason, this study has the aim of being able to analyze fleet macth for optimum productivity by minimizing obstacles that occur such as hauling roads that are not standardized by the Ministerial Decree No. 1827/K/30/MEM/2018, slipperly handling, road maintenance, front maintenance, truck queue which results in high cycle times that occur.The percentage of achievement of the productivity target based on the planned overburden stripping in July was 545,669 Bcm. Meanwhile, based on the actual results, only 222,276 BCM. The result is less than half of the plan that has been targeted. One of the causes of not achieving the production target is in the location preparation mechanism, lack of supervision, the number of breakdown units, the effect of site preparation and the effect of the compatibility of the number of equipment.From the observations in the field and the calculation of the compatibility factor between the excavator and the dumptruck, it was found that the MF result was 0.94 < 1, meaning that the excavator loading equipment worked less than 100% while the dumptruck transportation equipment worked 100%, so there was a waiting time for the loading equipment. Thus, if optimization is carried out on the effective work of the tool, evaluation of working hours and selection of healthy units can increase production results so that targets can be met. Abstrak. PT Nunukan Bara Santosa Satu (NBSS) adalah badan usaha swasta milik Medco Minning dengan komoditas yang penghasil batubara, kegiatan penambangan, pengolahan serta lebih lanjut melakukan pemasaran dari komoditas batubara yang terletak di Desa Sebakis, Kecamatan Nunukan, Kabupaten Nunukan, Provinsi Kalimantan Utara, untuk menunjang proses penambangan, pada site Ambu menggunakan alat angkut dengan jenis Dump Truck Sany SKT 90 dengan alat gali muat Sany 750H, dengan metode tambang terbuka open pit, sehingga dalam seluruh kegiatan penambangan terdapat faktor yang sulit untuk dihindari yaitu cuaca, jika terjadinya hujan akan mengakibatkan berhentinya produksi dikarenakan dengan kondisi jalan yang masih tanah serta dalam penanganan sliperly nya masih kekurangan unit, akan tetapi hal tersebut bisa ditutupi dengan kondisi cuaca yang cerah. Untuk itu penelitian ini memiliki tujuan agar dapat menganalisa fleet macth untuk productivity yang optimum dengan meminimalisir hambatan yang terjadi seperti jalan hauling yang kurang standar dengan peraturan Kepmen No.1827/K/30/MEM/2018, penanganan sliperly, road maintenance, front maintenance, truck queue yang mengakibatkan tingginya cycle time yang terjadi. Persentase ketercapaian target produktivitas berdasarkan rencana pengupasan lapisan tanah penutup (Overburden) pada bulan Juli sebesar 545.669 Bcm. Sedangkan berdasarkan hasil aktualnya hanya sebesar 222.276 BCM. Hasil tersebut kurang dari setengahnya dari rencana yang telah ditargetkan. Penyebab tidak tercapainya target produksi salah satunya yaitu dalam mekanisme penyiapan lokasi, kurangnya pengawasan, banyaknya unit yang breakdown, pengaruh penyiapan lokasi dan pengaruh keserasian jumlah alat. Dari hasil pengamatan di lapangan dan hasil perhitungan faktor keserasian antara excavator dan dumptruck didapat bahwa hasil MF sebesar 0,94 < 1, artinya alat muat excavator bekerja kurang dari 100% sedangkan alat angkut dumptruck bekerja 100%, sehingga terdapat waktu tunggu bagi alat muat. Dengan demikian jika dilakukan optimasi terhadap kerja efektif alat tersebut, evaluasi jam kerja dan pemilihan unit yang sehat dapat meningkatkan hasil produksi sehingga target dapat terpenuhi.